Vocabulary size research at Victoria University of Wellington, New Zealand. (3rd June 2014) - Nation, Paul; Coxhead, Averil
<x content-type="archive" xml:space="preserve">Abstract</x> The English Language Institute (now the School of Linguistics and Applied Language Studies) at Victoria University of Wellington has a long history of corpus-based vocabulary research, especially after the arrival of the second director of the institute, H. V. George, and the appointment of Helen Barnard, whom George knew in India. George's successor, Graeme Kennedy, also saw corpus linguistics as a very fruitful and important area of applied language research.